Advances on Scoliogeny, Diagnosis and Management of Scoliosis and Spinal Disorders - Grivas, Theodoros B. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book contains research articles on the advances in the aetiology of idiopathic scoliosis (IS), the spinal growth related to the implementation of growth modulation for the surgical treatment of early-onset IS, the non-surgical treatment of IS using Physiotheraputic Scoliosis Specific Exercises, and braces. Additionally, it focuses on issues related to surgical treatment, issues related to body posture and the quality of life of this sensitive group of people. The high quality of published papers in this Special Issue of the JCM serve these objectives.